2017
DOI: 10.2169/internalmedicine.56.7593
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Storm Precipitated by Diabetic Ketoacidosis and Influenza A: A Case Report and Literature Review

Abstract: A 46-year-old woman with a history of Graves' disease presented with the chief complaints of appetite loss, weight loss, fatigue, nausea, and sweating. She was diagnosed with diabetic ketoacidosis (DKA), thyroid storm, and influenza A. She was treated with an intravenous insulin drip, intravenous fluid therapy, intravenous hydrocortisone, oral potassium iodine, and oral methimazole. As methimazole-induced neutropenia was suspected, the patient underwent thyroidectomy. It is important to maintain awareness that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The full-texts of the remaining 28 reports were studied, and 7 were excluded due to mismatch with the selection criteria (absence of thyroid storm − 4, absence of DKA - 3). Finally, 21 reports were subsequently selected which had 26 cases [10, 11, 3351] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full-texts of the remaining 28 reports were studied, and 7 were excluded due to mismatch with the selection criteria (absence of thyroid storm − 4, absence of DKA - 3). Finally, 21 reports were subsequently selected which had 26 cases [10, 11, 3351] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…We aim to systematically review cases reported on concurrent presentation of TS and DKA concerning its presentation, investigations and management. In 2009 (9 cases) and 2017 (18 cases), two separate summaries on concurrent presentation of TS and DKA were reported along with similar case reports [10, 11]. However, this systemic review includes additional cases and an in-depth analysis.…”
Section: Introductionmentioning
confidence: 99%
“…DKA usually occurs as a consequence of absolute or relative insulin deficiency that is accompanied by an increase in counterregulatory hormones (glucagon, cortisol, growth hormone, and epinephrine). This hormonal imbalance enhances hepatic gluconeogenesis, glycogenolysis, and lipolysis [1,2,3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous presentation of thyrotoxicosis and diabetic ketoacidosis (DKA) have been reported several times, but it is a clinically unusual situation and remains a diagnostic challenge in clinical practice, because both entities share similar manifestations [1,2,3,4,5,6]. Concurrent presentation of DKA, thyroxin (T 4 ) toxicosis and thyrotoxic cardiomyopathy is even rarer.…”
Section: Introductionmentioning
confidence: 99%
“…11 The literature related to TS was searched from 2016 to 2019, and the clinical characteristics of gastrointestinal symptoms in patients with TS were found to mainly be nausea, and the main cause of TS to be Graves' disease with unknown or poor compliance with anti-thyroid drugs (Table 3). [33][34][35][36][37][38][39][40][41][42][43][44][45][46] Considering that hiccups are not common in either DKA or TS, we speculate that the incidence of intractable hiccups is rare when DKA overlaps with TS. By carefully searching the literature, we found the following related cases.…”
Section: Case Presentationmentioning
confidence: 99%